HUBUNGAN PENGETAHUAN IBU DAN ASUPAN MAKAN TERHADAP STATUS GIZI ANAK PESERTA POS GIZI DI PUKESMAS BAJA KOTA TANGERANG - Auliany, Diah; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The toddler period is commonly known as the golden age or the golden age because the success of growth and progress in the future is determined at this time. The nutritional status of toddlers is an important thing that every parent should know. The purpose of this study was to determine the relationship between a mother's knowledge and a toddler's food intake with a toddler's nutritional status (weight/age, height/age, and weight/height). This research is an analytic observational study with a cross-sectional design. This research was conducted in June 2023 in the working area of ​​the Jalan Baja Health Center, Tangerang City. The sample in this study used Saturated Sampling with as many as 63 respondents. The statistical analysis used was univariate analysis and bivariate analysis with chi-square. The results showed that 23.8% of respondents had wasting nutritional status, 71.4% of respondents had good knowledge and 50.8% had frequent food intake. There is a significant relationship between knowledge (p=0.031) and food intake (p=0.021) with the nutritional status of toddlers. From this study it can be concluded that there is a relationship between the mother's knowledge of nutritional status, and food intake and nutritional status with 3 indices, namely (BB/A), (TB/A), and (BB/TB). Suggestion: To improve the nutritional status of toddlers, it is best to increase mothers' knowledge about nutrition by counseling mothers of toddlers about selecting and processing food that is diverse, nutritionally balanced, and high in animal protein.